Interpretive Paradigm in Psychology - Nelly Marhayati (Program Studi Psikologi Islam, 2020)
The Purpose of this article is to know interpretive paradigm in Psychology. When researchers examine cultural behavior, especially the experience of individuals then to detect and describe some aspects of the implied culture, hidden rules, the meaning of rituals and worship in a cultural society, they should use interpretive paradigm. The interpretive paradigm in the field of psychology is a foundation for qualitative research methods. A qualitative approach can be used when the researcher understands the informants’ point of view more deeply, dynamically and will explore various factors simultaneously and can be used in informal situations. There are four types of qualitative research paradigms namely ethnography, case studies, phenomenology and grounded theory.